Literatur Review: Plant Efficacy as Biolarvicide for Anopheles Mosquito Vector Control: Literatur Review: Efikasi Tanaman Sebagai Biolarvasida Untuk Pengendalian Vektor Nyamuk Anopheles - Asrianto Asrianto; Suarna Samai; Muhamad Sahidin; Indra Taufik Sahli; Risda Hartati; Wiwiek Mulyani (Jurnal Sains dan Kesehatan, 2023)
Mosquito vectors are a severe threat to the prevalence and incidence of malaria, dengue fever, yellow fever, and filariasis. Malaria is a Plasmodium infection that is transmitted by the female Anopheles mosquito. Malaria cases in tropical and subtropical countries have social and economic impacts. Mosquito vector control has been using chemical and synthetic compounds. This method can reduce malaria cases, but it creates new problems that also slow down the elimination of malaria in the long run. Vector control in the larval phase using bioactive compounds of various plants is an alternative to eradicating vectors; besides that, utilizing these bioactive compounds is relatively safer, cheaper, and more accessible. Plants contain several compounds that are toxic to Anopheles mosquito larvae. This literature study summarizes research on extracts of various plants that function as larvicides of the Anopheles mosquito. The research method uses a literature study. The literature related to the research topic was obtained from the databases of Google Scholar, Semantic Sholar, Garuda, PubMed, and Science Direct. The primary literature is a publication of the last ten years. The literature study results showed that the plants Vitex negundo Linn., Lawsonia inermisLinn., Stachys byzantina K.Koch., Pithecellobium dulce Bth., Olax dissitiora Oliv., Ipomea cairica Linn., Ricinnus communis Linn., Carica papaya Linn., Paederia foetida Linn., Glycosmis pentaphylla Retz., Terminalia chebula Retz., Annona squamosa Linn., Tagetes erecta Linn. and Azadiracha indica Juss. against mosquito vectors. This study concludes that secondary plant metabolites can be used as candidates and alternatives for controlling Anopheles mosquito larvae.